The influence of music therapy on mental well-being among postoperative patients of total knee arthroplasty (TKA) - Aris, Aishairma; Sulaiman, Suliza; Che Hasan, Muhammad Kamil (Elsevier, 2019)
Objective The objective of this study was to investigate whether music therapy affects immediate postoperative well-being among patients who had undergone TKA surgery in the recovery unit.